Short Communication: Cyrtodactylus elok Dring, 1979 (Sauria, Gekkonidae): A first country record for Thailand - YODCHAIY CHUAYNKERN; PECHRKAWIN NURNGSOMSRI; CHANTIP CHUAYNKERN; PRATEEP DUENGKAE; SUNATE KARAPHAN (Biodiversitas Journal of Biological Diversity, 2018)
Chuaynkern Y, Nurngsomsri P, Chuaynkern C, Duengkae P, Karaphan S. 2018. Short Communication: Cyrtodactylus elok Dring, 1979 (Sauria, Gekkonidae): A first country record for Thailand. Biodiversitas 19: 2111-2117. The present work reports a new country record for Thailand of the bent-toed gecko Cyrtodactylus elok Dring, 1979 based on a single specimen which was collected from Hala?Bala Wildlife Sanctuary, Narathiwat Province (southern Thailand). The Thai specimen shows morphological characters similar to C. elok as follows: 12-14 supralabials, 10-11 infralabials, seven tubercles across midbody, 49 ventral scales, enlarged femoral scales absent, tubercles on forelimbs absent, ventrolateral fold poorly defined, and large tubercles of dorsolateral caudal rows. The species was previously known from the discovery made in Malaysia. This addition brings the number of Thai prehensile-tailed species to three. Morphological and distributional maps are provided.